Managing Higher Vertebrate Pest Problem in Indian Agriculture: Time to Rethink: OPINION PAPER - Chaudhary, Vipin (Annals of Arid Zone, 2025)
Indian agriculture is facing growing challenge from the higher vertebrate pests as they cause widespread damage to agricultural crops and thereby affect the food security of the country. Crop raiding by different wild animals particularly, Monkeys (Macaca sp.); Hanuman langur (Presbytis entellus), Elephant (Elephas maximus), Blue bull (Boselaphus tragocamelus), Sambar deer (Cervus unicolor), Black buck (Antilope cervicapra), Chinkara (Gazellaga zellabennetti), Wild boar (Sus scrofa), peacock/parakeets, porcupine (Hystrix indica) etc. has been widely reported from all over the country (Agrawal et al., 2016). Wild boars and nilgai are responsible for large scale crop damages annually in some states like Bihar, Rajasthan, and Uttar Pradesh (Manral et al., 2016). Despite having tremendous impact on agricultural productivity and rural livelihoods, their management is still constraint by legal, socio-cultural, weak institutional coordination, and a lack of effective, science-based interventions. This article highlights the current management strategies, identifies the critical constraints and presents the acceptable solutions.